How Green Space Justice in urban built-up areas affects public mental health: a moderated chain mediation model - Dong, Tian; Zhong, Qikang; Yue, Bangguo (Frontiers in Public Health, 2024)
Background Green and blue spaces, as crucial components of urban ecosystems, significantly impact the physical and mental health of residents. However, the mechanisms through which Green/Blue Space Justice influence residents’ health remain unclear. Methods This study aims to explore the impact of green spaces on public psychological responses, physical activity, and mental health from a justice perspective, and to examine the moderating role of blue spaces in this relationship. The research was conducted in selected communities within the Chang-Zhu-Tan urban agglomeration in Hunan Province, China. A total of 801 valid questionnaires were collected through field visits and online surveys. The study uses an improved Gaussian-based two-step floating catchment area (2SFCA) method to assess green space accessibility. Data were analyzed using structural equation modeling (SEM) and moderation effect analysis to reveal the relationships between variables. Results The findings indicate that Green Space Justice has a significant positive impact on psychological responses, physical activity, and mental health; psychological responses and physical activity play crucial mediating roles between Green Space Justice and mental health; and Green Space Justice significantly affects mental health through a chain mediation path involving psychological responses and physical activity. Moreover, Blue Space Justice significantly moderates the impact of Green Space Justice on psychological responses and physical activity, but does not have a significant direct impact on mental health. Conclusion This study enriches the theory of Green Space Justice by revealing the mechanisms through which it influences mental health via psychological responses and physical activity. It provides a scientific basis for the development of healthy cities. Additionally, it recommends that urban planning should prioritize the equitable distribution and high accessibility of both green and blue spaces to comprehensively enhance residents’ physical and mental well-being. Policymakers should consider prioritizing the accessibility of high-quality green spaces for vulnerable communities during urban renewal and expansion processes to reduce social health inequalities and promote broader public health outcomes.